U–commerce research: a literature review and classification. (4th March 2013) - Liu, Qihua
Nowadays, numerous journals and conferences have published articles related to ubiquitous commerce (u–commerce), indicating many researchers' interest. Therefore, the goal of this paper is to review the works that were published in journals and conferences, suggest a new classification framework of ubiquitous commerce research and explore each feature of classification framework. This paper is based on a literature review of ubiquitous commerce research from 2000 to 2010 using a keyword index and paper title search. The 209 articles are classified and results of these are presented, based on a framework that consists of five distinct layers: theory and research layer, network infrastructure layer, technology infrastructure layer, application layer and user infrastructure layer. This paper allows researchers to extract several lessons learned that are important for the ubiquitous commerce research.